POLITIK HUKUM PIDANA TENTANG PENGATURAN TINDAK PIDANA DI INDONESIA DALAM KASUS NARKOTIKA - Andri Koswara (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This study was conducted with the aim of being able to analyze legal politics in regulating illegal drugs and narcotics in Indonesia. This research will be carried out using a normative legal approach and will focus on an inventory of positive law, legal findings in cases in concreto, legal comparisons, legal principles and doctrines, legal history, and legal systematics. The data in this study came from various primary and secondary legal data. The primary legal data in this article comes from various laws and regulations that are still relevant to the subject of discussion, such as Law Number 35 of 2009 concerning Narcotics. The secondary legal data is in the form of various understandings of law in primary data. The results of this study found that narcotics legal politics is the core of the formation of a legal system that contains laws and regulations that will regulate various criminal acts. In Articles 111 and 112, there is a fairly severe prison sentence, in which imprisonment for a minimum of 4 years and a maximum of 20 years, up to the death penalty.